2019
DOI: 10.33224/rrch/2019.64.5.03
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling for kinetics of Fe3+ exchange on pretreated analcime

Abstract: The kinetics of the ion-exchange process with iron on pretreated analcime has been investigated in different conditions of temperature, time and concentration of the exchange solution. The performances of the catalyst were analyzed using the Table Curve software. The mathematical model corresponding to the characteristic equation provides a good arrangement of the experimental points on the responding surface, simplicity of the characteristic equation and a good determination coefficient that is near unity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Although Na, Ca, and Fe cations could vary majorly as the acid concentration rises, Mg and K cations could move away partially only since they had a stronger bond with the analcime. The SiO 2 /Al 2 O 3 ratio increased from 4.62 to 6.15 as a result of acid treatment [ 14 , 17 , 19 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Na, Ca, and Fe cations could vary majorly as the acid concentration rises, Mg and K cations could move away partially only since they had a stronger bond with the analcime. The SiO 2 /Al 2 O 3 ratio increased from 4.62 to 6.15 as a result of acid treatment [ 14 , 17 , 19 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Park et al [ 14 ] found that the specific surface area and micropore volume of analcime treated with 1 N HCl solution increased from 16 to 119 m 2 /g and from 0.02 to 0.09 cm 3 /g, respectively. Cobzaru et al [ 17 ] showed that the specific surface area and micropore volume of analcime zeolite were 14.649 m 2 /g and 0.001 cm 3 /g respectively, and they increased to 89.473 m 2 /g and 0.029 cm 3 /g for 1 N HNO 3 acid-treated analcime.…”
Section: Introductionmentioning
confidence: 99%
“…In order to create a mathematical equation corresponding to different experimental research, many works have been conducted and are presented in the specialized literature [27][28][29][30]32,[36][37][38][39]. However, a rather difficult problem arises when it is desired to identify a mathematical equation that corresponds to several studies: -Studies that were carried out at different times or in different locations but at the same time; -Studies conducted by different authors but which have the same research field.…”
Section: Introductionmentioning
confidence: 99%
“…In order to create a mathematical model corresponding for study, many works have been made and are presented in the specialized literature [28,29,31,32,34,38,[41][42][43][44], but a rather difficult problem arises when it is desired to identify a mathematical model that corresponds to several studies: -Studies that have been performed at different time intervals or in different locations but at the same time; -Studies conducted by different authors, but which have the same research field.…”
Section: Introductionmentioning
confidence: 99%